2001
DOI: 10.2307/2666132
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Striga (Scrophulariaceae) in Africa

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Missouri Botanical Garden Press is collaborating with JSTOR to digitize, preserve and extend access to Annals of the Missouri Botanical Garden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 7 publications
1
89
0
1
Order By: Relevance
“…(Matusova et al, 2004), a very low germination rate (<10 %) has been found in the absence of hosts in all cases. The system of chemical recognition assures that germination begins only when the root of the potential host is available in the immediate vicinity (Mohamed et al, 2001;Joel et al, 2011). The formation of haustoria also occurs in answer to chemical and tactile stimuli provided by the host roots (Westwood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Matusova et al, 2004), a very low germination rate (<10 %) has been found in the absence of hosts in all cases. The system of chemical recognition assures that germination begins only when the root of the potential host is available in the immediate vicinity (Mohamed et al, 2001;Joel et al, 2011). The formation of haustoria also occurs in answer to chemical and tactile stimuli provided by the host roots (Westwood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The herbarium and literature data provided information on the geographical distribution of different parasitic weed species (e.g. Mohamed et al 2001;Rodenburg et al 2014Rodenburg et al , 2015. We found out that Striga species are spread over 33 African countries that produce rice in the rainfed uplands where these species can be encountered.…”
Section: Evaluating the Institutional Dimension Of Parasitic Weeds Anmentioning
confidence: 79%
“…This is where it infects the major cereal crops: maize, sorghum, rice and finger millet. S. asiatica is predominantly found in the coastal region infecting upland rice (Gethi et al, 2005) and exists sporadically in Isiolo, Busia and Naivasha (Mohamed et al, 2001). Striga gesneriodes, a species adapted as a pest of legumes has a wide geographical distribution in Kenya compared to the other species.…”
Section: Introductionmentioning
confidence: 99%